Pemaknaan Second Account Instagram Pada Generasi Z: Studi Mahasiswa FISIP Universitas Muhammadiyah Bengkulu - Pramesti, Melany; Wijayanti, Ayu; Safitra, Linda (Prodi Sosiologi FISIP Universitas Teuku Umar, 2025)
The phenomenon of using second accounts on Instagram is growing among students, especially in generation Z, to express themselves more freely and personally. The purpose of this research is to understand the meaning of students of the Faculty of Social and Political Sciences, Universitas Muhammadiyah Bengkulu regarding the use of second accounts on Instagram, with a qualitative approach and phenomenological method. Dramaturgical theory was used as the theoretical basis to analyze how individuals present themselves in social interactions, by distinguishing between “front stage” and “back stage” in the use of social media. Data were obtained through in-depth interviews, participant observation, and documentation of students who actively use second accounts on Instagram. The research findings show that university students use second accounts as a private place to express feelings, stage totality: front and back stage working together and an escape from social pressure and aesthetic standards. Second accounts are considered as a symbol of a truer self-identity and as a tool to build closer social relationships with certain groups of friends. The use of second accounts also reflects students' strategies in managing self-image and privacy in the digital world. Through the perspective of dramaturgical theory, the use of second accounts is understood as the result of different self-presentations on the